The Effectiveness of the ”Creative Thinking Course” in [eveloping Creative Thinking Abilities of a Sample of Students in the Kingdom University in Bahrain - Adnan M. Al Qadhi (Journal of Educational and Psychological Studies, 2017)
The aim of this study was to identify the effectiveness of the Creative Thinking Course (38121 on developing creative thinking skills (fluency, originality, elaboration, titling, resistance of closure, and the strength of creativity) in Bahraini University Students in the University of Kingdom. The study was based on a quasi-experimental method. Participants were (N=44) university students, (N= 24 female and N= 20 male). Torrance test of creative thinking (non-verbal A & B). Accordingly, this study attempted to verify the following hypothesis: Creative thinking skills are more improved after taking the Creative Thinking Course (38121. The study also sought to examine the differences between females and males in developing their creative thinking skills. The results indicate the effectiveness of the proposed training course in all creative thinking skills. There were significant differences (0.001) in the experimental group on post- non- verbal Torrance test (A, B) in all creative skills, which support the hypotheses of the study. There were no statistically significant differences related to gender differences.